2017
DOI: 10.19080/aibm.2017.06.555680
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of E. coli From Diarrheic Calves and Their Antibiotic Sensitivity Test in Selected Dairy Farms of Debre Zeit, Ethiopia

Abstract: A cross-sectional study was conducted in 9 dairy farms in and around Debre Zeit from November 2015 to April 2016 with the major objective to estimate the prevalence of E. coli from diarrheic calves up to six months of age and assessment of risk factors associated with calf diarrhea as well as antimicrobial sensitivity testing. Fecal samples were collected directly from the rectum of diarrheic calves and isolation and identification of the bacterium were confirmed on the basis of their morphology, staining, cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
6
2
1
Order By: Relevance
“…Moreover, similar results were reported by [ 49 ] (44%) and [ 50 ] (45.8%) in Bangladesh. However, our isolation rate was proportionally lower than the recent works of [ 23 ] and [ 1 ], which stated 70.7% and 76.45% prevalence of E . coli before molecular analysis.…”
Section: Discussioncontrasting
confidence: 86%
“…Moreover, similar results were reported by [ 49 ] (44%) and [ 50 ] (45.8%) in Bangladesh. However, our isolation rate was proportionally lower than the recent works of [ 23 ] and [ 1 ], which stated 70.7% and 76.45% prevalence of E . coli before molecular analysis.…”
Section: Discussioncontrasting
confidence: 86%
“…The time between birth and the first feeding is the prime factor for the failure of passive transfer of colostral immunity. Another study conducted in Ethiopia also reported that calf mortality is significantly higher in those that got colostrum late after birth [ 26 ]. A higher infection rate of BRV (8.3%) and BCoV (4.2%) was observed in farms that gave colostrum below 1 liter.…”
Section: Discussionmentioning
confidence: 99%
“…123 diarrheic calves reared within 53 farms in Kombolcha, Dessie and Haik, were sampled where each sites accounted for 55, 59 and 9 calves respectively. For the sake of distinguishing risk factors, calves were classi ed based on farm size(head of dairy cows) as small (<5), medium (6-50) and large (>50); age (wk/s) of calves (≤1, 2-4, 4-6, and 6-12) [11], breed(local, cross and exotic) and sex. Calves were found kept with their dam or in isolated pens for the whole day.…”
Section: Study Populationmentioning
confidence: 99%
“…Consequently, high mortality rate associated with various infectious agents in calves under 3-weeks-old and up to 3-months-old has been reported [9]. E. coli is the most important cause of bacterial scours in calves [11] and poses a signi cant treatment cost, genetic loss and impaired future performance. Although a study based on culture and biotyping has been carried out in Kombolcha previously, E. coli has never been studied in adjacent cosmopolitan areas of Dessie and Haik.…”
Section: Introductionmentioning
confidence: 99%